COVID-19 pandemic: Trend analysis with respect to District Anantnag, Jammu and Kashmir, Northern India - Mehbooba Rasool; Mohsina Mukhtar; Iftikhar Hussain Munshi; Muneer Ahmad Masoodi; Mohammad Yousuf Zagoo; Imtiyaz Ahmad (Wolters Kluwer Medknow Publications, 2022)
With 1st case being reported in Wuhan city of China in December 2019, COVID-19 infection cases made their way to every corner of the world. Then, on January 07, 2020, laboratory results led to pneumonia being named as COVID-19. Scant data is available from Northern India, thus to reveal the trend of COVID-19 infection since last year of COVID-19 pandemic onset, this study took shape. The unit of analysis of our study was District Anantnag, Jammu and Kashmir. Till February 05, 2021, a total of 4625 cases of COVID-19 virus were reported in District Anantnag, Jammu and Kashmir. Negative history of close contact with COVID-19 patient (66.1%) constituted the most common exposure, majority (84.4%) were asymptomatic and comorbidities were present in 68 (1.5%). COVID-19 infection was more prevalent among younger age group, with higher male predominance, with comorbid being at higher risk, hence most stringent measures must be adopted.